Colorectal Serrated Neoplasia: An Institutional 12-Year Review Highlights the Impact of a Screening Programme. (6th February 2019) - McCarthy, A. J.; O'Reilly, S. M.; Shanley, J.; Geraghty, R.; Ryan, E. J.; Cullen, G.; Sheahan, K.
Abstract : Background . As the malignant potential of sessile serrated lesions/polyps (SSL/Ps) and traditional serrated adenomas (TSAs) has been clearly demonstrated, it is important that serrated polyps are identified and correctly classified histologically. Aim . Our aim was to characterize the clinicopathological features of a series of SSL/Ps & TSAs, to assess the accuracy of the pathological diagnosis, the incidence, and the rate of dysplasia in SSL/Ps & TSAs. Methods . We identified all colorectal serrated polyps between 01/01/2004 and 31/05/2016, by searching the laboratory information system for all cases assigned a "serrated adenoma" SNOMED code. All available and suitable slides were reviewed by one pathologist, who was blinded to the original diagnosis and the site of the polyp. Subsequently discordant cases, SSL/Ps with dysplasia, and all TSAs were reviewed by a second pathologist. Results . Over a 149-month period, 759 "serrated adenoma" polyps were identified, with 664 (from 523 patients) available for review. 41.1% were reviewed by both pathologists; 15.1% (100/664) were reclassified, with the majority being changed from SSL/P to hyperplastic polyp (HYP) (66/664; 9.9%). 80.3% of these HYPs were located in the left colon, and the majority exhibited prolapse effect. There were 520 SSL/Ps (92.2%) & 40 TSAs (7.1%). The majority of SSL/Ps were in the right colon (86.7%) and were small (64.5% <1 cm), while most TSAs were in the left colon (85.7%) and were large (73.1 % ≥ 1   cm ). 6.7% of SSL/Ps exhibited dysplasia, the majority of which were large (66.7 % ≥ 1   cm ). Following consensus review, 13/520 (2.5%) SSL/Ps were downgraded from SSL/P with dysplasia to SSL/P without dysplasia. Detection of SSL/Ps peaked in the most recent years reviewed (87.5% reported between 2013 and 2016, inclusive), coinciding with the introduction of "BowelScreen" (the Irish FIT-based colorectal cancer screening programme). Conclusions . Awareness of, and adherence to, diagnostic criteria is essential for accurate classification of colorectal polyps.